Targeted next-generation sequencing of the 16S-23S rRNA region for culture-independent bacterial identification - increased discrimination of closely related species - Artur J. Sabat (Nature Portfolio, 2017)
Abstract The aim of this study was to develop an easy-to-use culture-free diagnostic method based on next generation sequencing (NGS) of PCR amplification products encompassing whole 16S-23S rRNA region to improve the resolution of bacterial species identification. To determine the resolution of the new method 67 isolates were subjected to four identification methods: Sanger sequencing of the 16S rRNA gene; NGS of the 16S-23S rRNA region using MiSeq (Illumina) sequencer; Microflex MS (Bruker) and VITEK MS (bioMérieux). To evaluate the performance of this new method when applied directly on clinical samples, we conducted a proof of principle study with 60 urine samples from patients suspected of urinary tract infections (UTIs), 23 BacT/ALERT (bioMérieux) positive blood culture bottles and 21 clinical orthopedic samples. The resolution power of NGS of the 16S-23S rRNA region was superior to other tested identification methods. Furthermore, the new method correctly identified pathogens established as the cause of UTIs and blood stream infections with conventional culture. NGS of the 16S-23S rRNA region also showed increased detection of bacterial microorganisms in clinical samples from orthopedic patients. Therefore, we conclude that our method has the potential to increase diagnostic yield for detection of bacterial pathogenic species compared to current methods.